PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA DIMEDIASI MOTIVASI KERJA PADA GURU- GURU SMK MA’ARIF COMAL PEMALANG - Samtono Samtono (Among Makarti, STIE AMA Salatiga, 2018)
AbstractThis study as to determine the effect work environment, job satisfaction, on work motivation, and its impac t on teacher ferformance in teacher’s performance SMK Ma’arif Comal Pemalang Data were obtained through a questionare. The sample used in the study were 95 respondents. The data obtained were processed using descriptive analysis and quantitative statistical anaylisis. Quantitative analysis using mutiple regression analysis to determine the effect of independent variables on the dependent variable, bu t before the tes t is done first tested the validity and reliability testing. Regression analysis showed that work environment, job satisfaction, and work motivation not affect the performance SMK Ma’arif Comal Pemalang. Keywords : Work environment, job satisfaction, work motivation, performance